2019
DOI: 10.1039/c8cc10091h
|View full text |Cite
|
Sign up to set email alerts
|

DEAD-box RNA helicases Dbp2, Ded1 and Mss116 bind to G-quadruplex nucleic acids and destabilize G-quadruplex RNA

Abstract: DEAD-box RNA helicases Dbp2, Ded1 and Mss116 bind to G-quadruplex nucleic acids and destabilize G-quadruplex RNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 41 publications
2
27
0
Order By: Relevance
“…A genome-wide study in yeast showed that Ded1 unwinds mRNA secondary structure in the 5′UTR during scanning of the 43S pre-initiation complex and prevents the use of near-cognate start codons that are proximal to such structures, allowing efficient translation of the main ORF [ 73 ]. DDX3X can also enhance IRES activity [ 74 ] and destabilize G-quadruplexes [ 75 , 76 ]. Intriguingly, recent studies propose a role of DDX3X in promoting [ 77 ] or repressing [ 78 ] repeat-associated, non-AUG (RAN) translation.…”
Section: De Novo Variants In Ddx3x Are Thmentioning
confidence: 99%
“…A genome-wide study in yeast showed that Ded1 unwinds mRNA secondary structure in the 5′UTR during scanning of the 43S pre-initiation complex and prevents the use of near-cognate start codons that are proximal to such structures, allowing efficient translation of the main ORF [ 73 ]. DDX3X can also enhance IRES activity [ 74 ] and destabilize G-quadruplexes [ 75 , 76 ]. Intriguingly, recent studies propose a role of DDX3X in promoting [ 77 ] or repressing [ 78 ] repeat-associated, non-AUG (RAN) translation.…”
Section: De Novo Variants In Ddx3x Are Thmentioning
confidence: 99%
“…Many helicases have been found to possess dual unwinding activities, acting on both DNA and RNA substrates. Thus far, there are seven helicases exhibiting RG4-unwinding activity and two of them have been identified to unwind DG4 structure as well (Booy et al., 2012, Chakraborty and Grosse, 2011, Gao et al., 2019). We then asked whether MOV10L1 can also work on DG4 substrate.…”
Section: Resultsmentioning
confidence: 99%
“…Increasing evidence indicates that intramolecular RNA G-quadruplex (RG4) motifs are biologically relevant structures, and their occurrence can play vital roles in many key cellular functions, including telomere homeostasis, gene expression, and pre-mRNA processing (Agarwala et al., 2015, Bugaut and Balasubramanian, 2012, Cammas and Millevoi, 2017, Fay et al., 2017, Millevoi et al., 2012, Rhodes and Lipps, 2015, Simone et al., 2015). Even though several helicases and nucleases have been shown to remove DNA G-quadruplex (DG4) structure and regulate cellular processes (Baran et al., 1997, Chen et al., 2018, Harrington et al., 1997, Mendoza et al., 2016, Sauer and Paeschke, 2017, Sun et al., 1998, Sun et al., 1999), only a few RNA helicases, so far, have been reported to be capable of unwinding RG4 structures in vitro (Booy et al., 2012, Chakraborty and Grosse, 2011, Creacy et al., 2008, Gao et al., 2019, McRae et al., 2017, Ribeiro de Almeida et al., 2018). One of the reasons is that RG4 is a thermodynamically stable structure compared with other forms of RNA, thereby in requirement of specialized RNA helicase to resolve it (Hardin et al., 2000).…”
Section: Introductionmentioning
confidence: 99%
“…DDX is an important ATP-dependent RNA helicase family, which exists in almost all prokaryotes and eukaryotes ( 11 ). Furthermore, DDX plays an important role in RNA metabolism, it is required for RNA functions, including gene transcription, RNA precursor mothering, ribosome synthesis, RNA output, translation initiation and RNA degradation ( 12 , 13 ). Several DDX RNA helicase subtypes have been reported to be abnormally expressed in various cancer types ( 14 ).…”
Section: Discussionmentioning
confidence: 99%